Analysis of the crack development and shear transfer mechanisms of reinforced concrete beams with low amounts of shear reinforcement. (1st November 2020) - Tung, Nguyen Duc; Betschoga, Christoph; Tue, Nguyen Viet
Highlights: An analysis of crack development and shear transfer mechanisms in beams with low shear reinforcement is presented. A group of equilibrium conditions, geometric conditions and constitutive relationships are employed. The relative contributions of different shear mechanisms during the crack development are investigated. A simplified model for the shear resistance of rectangular beams is obtained. Comparison to the observed shear resistance of a large set of available test data is provided. Abstract: Although a sufficient quantity of shear reinforcement can improve the shear resistance of reinforced concrete beams, the shear failure of beams with a low amount of shear reinforcement is normally characterized by the formation of a single shear crack. In this case, it is not possible to make the basic assumptions inherent in the parallel chord truss analysis or the compression-field approaches, namely, that distributed shears cracks form a pattern of quasi-parallel shear cracks. As an extension of an approach to describing the critical shear crack formation within the critical shear band, this paper presents an analysis of crack development and shear transfer mechanisms in beams with a low amount of shear reinforcement. The starting point for the analysis was the shear cracking state, which was described in the previous stage of the development for beams without shear reinforcement. The shear crack development and shear resisting mechanisms were analyzed using a group of appropriate equilibrium conditions, geometric conditions and constitutive relationships. The proposed method was validated by comparing the predicted shear resistance with the test results for rectangular, simply supported beams subjected to point loads included in the ACI-DAfStb databases. Furthermore, the validated analysis was used to investigate the relative contributions of different shear resisting mechanisms during the shear crack development. Through regression analyses of the concrete contribution and the ultimate crack length, a simplified model for the shear resistance of rectangular beams with a low mount of shear reinforcement was obtained. Predictions using both the analytical and simplified models are in good agreement with the test results, providing suitable tools for the transition from beams without reinforcement to those with high quantities of shear reinforcement.